A real-time UWT-based intelligent fault detection method for PV-based microgrids - Yılmaz, Alper; Bayrak, Gökay (Elsevier Science Sa, 2019)
In this paper, a new un-decimated wavelet transform (UWT)-based fault detection method is proposed to overcome the limitations of WT-based methods in real-time applications. For the first time, UWT method is used to detect power quality disturbances (PQD) in microgrids in real time. UWT reduces the oscillations and noise in the signal and also is useful for selecting threshold values. This method is implemented by using only the voltage signal to detect the PQDs automatically for a PV-based microgrid. The voltage sag/swell, and interruption faults are evaluated in the experimental study by considering the duration and event amplitude of the PQD signal. High accuracy is also provided for detecting PQDs without using any noise filtering process. The results indicate that the proposed technique has a wide application area, fast fault detection time, and it is reliable for microgrids.
Keywords: Automatic fault detection; Un-decimated wavelet transform; Microgrid; Distributed generation; Data acquisition